One Hundred Days of Coronavirus Disease 2019 Prevention and Control in China. (5th June 2020) - Zhou, Lei; Wu, Zunyou; Li, Zhongjie; Zhang, Yanping; McGoogan, Jennifer M; Li, Qun; Dong, Xiaoping; Ren, Ruiqi; Feng, Luzhao; Qi, Xiaopeng; Xi, Jingjing; Cui, Ying; et al.
Abstract: The epidemic of novel coronavirus disease was first reported in China in late December 2019 and was brought under control after some 2 months in China. However, it has become a global pandemic, and the number of cases and deaths continues to increase outside of China. We describe the emergence of the pandemic, detail the first 100 days of China's response as a phase 1 containment strategy followed by phase 2 containment, and briefly highlight areas of focus for the future. Specific, simple, and pragmatic strategies used in China for risk assessment, prioritization, and deployment of resources are described. Details of implementation, at different risk levels, of the traditional public health interventions are shared. Involvement of society in mounting a whole country response and challenges experienced with logistics and supply chains are described. Finally, the methods China is employing to cautiously restart social life and economic activity are outlined. Abstract : The first 100 days of China's response to COVID-19 with specific, simple, and pragmatic strategies used for risk assessment, prioritization, and deployment of resources are critical for its rapid control of the epidemic and restarting of social life and economic activity.